2018
DOI: 10.14744/anatoljcardiol.2018.03604
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-21 abrogates palmitate-induced cardiomyocyte apoptosis through caspase-3/NF-kB signal pathways

Abstract: Objective:The aim of the study was to investigate the role of microRNA-21 (miR-21) in cardiomyocyte apoptosis and to determine a possible mechanism.Methods:H9c2 embryonic rat heart-derived cells were used in the study. Cell viability was determined using the 3-(4.5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay, and flow cytometry was used to evaluate cell apoptosis. Reverse transcription-polymerase chain reaction and western blot assays were used to detect mRNA and protein expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…As highlighted above, miR-21 participates in infarction injuries, cardiac remodeling, atherosclerosis, arrhythmias, and cardiomyopathy, which are caused by infection or metabolic disorders (Thum et al, 2008;Thum, 2012Thum, , 2014van Rooij and Olson, 2012;Fiedler and Thum, 2013;Li et al, 2016;Dai et al, 2018;Zhou et al, 2018). This indicates its potential as a clinical therapeutic target.…”
Section: Regulation Of Mirna-21 In Cvdsmentioning
confidence: 97%
See 2 more Smart Citations
“…As highlighted above, miR-21 participates in infarction injuries, cardiac remodeling, atherosclerosis, arrhythmias, and cardiomyopathy, which are caused by infection or metabolic disorders (Thum et al, 2008;Thum, 2012Thum, , 2014van Rooij and Olson, 2012;Fiedler and Thum, 2013;Li et al, 2016;Dai et al, 2018;Zhou et al, 2018). This indicates its potential as a clinical therapeutic target.…”
Section: Regulation Of Mirna-21 In Cvdsmentioning
confidence: 97%
“…The miR-21 expression is particularly elevated in highglucose-cultured CFs, which results in increased collagen crosslink and cardiac fibrosis via Jun amino-terminal kinases/stressactivated protein kinases (JNK/SAPK) and p38 by regulating dual specific phosphatase 8 (DUSP8) (Liu et al, 2014). On the contrary, Zhou et al (2018) reported that miR-21 was downregulated in palmitate-treated CMs. miR-21 protected CMs from apoptosis through inhibiting p65 and p-p38 expression.…”
Section: Cardiomyopathy: the Role Of Mir-21 In Cms And Cfsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, miR-21 expression levels were elevated in stress conditions such as oxidative stress, high glucose, and hypoxia (59)(60)(61)(62). However, oxygen-glucose deprivation (OGD) and palmitate exposure can considerably decrease miR-21 expression levels in cardiomyocytes (63,64).…”
Section: Vitro Study and Animal Model Studymentioning
confidence: 99%
“…Sequential activation of caspases plays a central role in the execution phase of cell apoptosis [15]. Previous studies have shown that proapoptotic members of caspase-8 were regarded as the initiators of apoptosis and caspase-3 was the executor and terminator of multiple apoptotic pathways [16][17][18][19]. Among the human inhibitors of apoptosis proteins (IAPs), X-chromosome-linked IAP (XIAP) is the most studied [20].…”
mentioning
confidence: 99%